Perspektif Konseling Pastoral Dalam Menghadapi Rasa Insecure Siswa Remaja Usia 15-18 Tahun - Edwin Goklas Silalahi; Nelson Hasibuan; Ampinia R. W. Rohy; Ruth Judica Siahaan; Junardi Seleleubaja (Sekolah Tinggi Teologi Ekumene Jakarta., 2024)
This study aims to explore the perspective of pastoral counseling in dealing with adolescents aged 15-18 years who experience insecurity, which can potentially affect their mental growth in the school environment. This research method uses a qualitative method with a library research approach. The study in the article covers several important aspects, including the description of insecurity in adolescents, the challenges faced in mental growth in that age range, the impact of unstable mental growth, the role of pastoral counseling in overcoming feelings of insecurity experienced by adolescents, and pastoral counseling strategies that can be applied. In the social and psychological context of adolescents, insecurity can be one of the complex problems and has a significant impact on their mental well-being. This study provides in-depth insights into the important role of pastoral counseling in helping adolescent students overcome insecurity and strengthen the mental development of adolescent students. The pastoral counseling perspective recognizes the importance of the spiritual dimension in adolescent life. Through this approach, pastoral counseling is able to help adolescents explore their values, beliefs, and meaning in life. They can also develop healthy coping skills, improve self-understanding, and create solid relationships with themselves and interaction relationships with others. Pastoral mentoring can provide youth with a safe space to talk about their concerns, feel heard, and gain a deep understanding of their identities and values.